2020
DOI: 10.1186/s13071-020-04363-0
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the presence of Ehrlichia canis DNA from different tissues of dogs with suspected subclinical ehrlichiosis

Abstract: Background Nowadays, Ehrlichia canis receives increasing attention because of its great morbidity and mortality in animals. Dogs in the subclinical and chronic phases can be asymptomatic, and serological tests show cross-reactivity and fail to differentiate between current and past infections. Moreover, there could be low parasitaemia, and E. canis might be found only in target organs, hence causing results to be negative by polymerase chain reaction (PCR) on blood samples. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…It would be advisable to perform DNA detection tests on tissue samples, other than blood, from animals considered suspicious of having a subclinical Ehrlichia canis infection. It could be useful to take tissue biopsies from lymph nodes, blood marrow, and/or spleen as previously suggested and to be performed in chronically infected canines, irrespective of the serological status to E. canis , where PCR of DNA extracted from splenic aspirates is reported to be a reliable method for determining the carrier state of Canine Monocytic Ehrlichiosis [ 36 ]. Differently, the use of seropositive but PCR negative dogs may be acceptable for A. phagocytophilum in areas endemic for Ixodes spp., since identification of seronegative donors may be difficult [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It would be advisable to perform DNA detection tests on tissue samples, other than blood, from animals considered suspicious of having a subclinical Ehrlichia canis infection. It could be useful to take tissue biopsies from lymph nodes, blood marrow, and/or spleen as previously suggested and to be performed in chronically infected canines, irrespective of the serological status to E. canis , where PCR of DNA extracted from splenic aspirates is reported to be a reliable method for determining the carrier state of Canine Monocytic Ehrlichiosis [ 36 ]. Differently, the use of seropositive but PCR negative dogs may be acceptable for A. phagocytophilum in areas endemic for Ixodes spp., since identification of seronegative donors may be difficult [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This failure would be likely due to a low degree of parasitemia [ 14 ] and was unremarkable given the sample population likely in the subclinical phase of E. canis infection. It is also important to note that PCR tests using peripheral blood samples can fail to detect E. canis during the subclinical stage of infection due to the marginalization of the pathogen in certain organs, such as the spleen, liver, and bone marrow [ 46 ]. Therefore, our results may have underestimated the occurrence of E. canis in the sample population.…”
Section: Discussionmentioning
confidence: 99%
“…These rates are much higher than those of Tran et al[3] when reporting 37/86 (43.02%) dogs with clinical signs of E. canis infection. In another study, Rodríguez et al[13] also found that 53/120 dogs showed signs of E. canis infection (44.1%). Our infected rate was also higher than that of Erdeger et al[5] reporting 91 dogs with a positive rate of 50.55%.…”
mentioning
confidence: 87%
“…Nowadays, the disease receives increasing attention because of its worldwide occurrence, prevalence throughout the year, morbidity, and mortality. Furthermore, this disease attracted scientists from different parts of the globe, such as Brazil [1,12,13], Malaysia [11], and India [14], because of its complex dissemination.…”
Section: Introductionmentioning
confidence: 99%